TWO-WHEELED MOTORIZED VEHICLE SECURITY USING E-KTP - Kartika; Misriana; Henny Irawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Motor vehicle theft from year to year always increases, both when parked and while being driven. Data from the National Police Headquarters for the period 1 to 7 May 2022 recorded 118 cases, and increased to 309 cases in the period 8 May to 14 May 2022. Based on the problem with the increase in motorized vehicle theft, a system is needed that can protect motorized vehicles from these theft cases. In this article we propose an additional system for electronic motorized vehicles. This system consists of additional controls, namely an e-KTP and touch screen, while the switch for the front brake already exists in motorized vehicles. After the ignition is turned on, the driver must press the touch screen button, press the front brake, attach the e-KTP to the RFId reader, each maximum time span for 50 seconds. If it is not in the sequence and the time is more than 50 seconds it will cause the motorized vehicle's horn to sound. After connecting, making controls and testing, the control system can work perfectly..